2020
DOI: 10.1080/19491034.2019.1710321
|View full text |Cite
|
Sign up to set email alerts
|

Hyperosmotic stress:in situchromatin phase separation

Abstract: Dehydration of cells by acute hyperosmotic stress has profound effects upon cell structure and function. Interphase chromatin and mitotic chromosomes collapse ("congelation"). HL-60/S4 cells remain~100% viable for, at least, 1 hour, exhibiting shrinkage to~2/3 their original volume, when placed in 300mM sucrose in tissue culture medium. Fixed cells were imaged by immunostaining confocal and STED microscopy. At a "global" structural level (μm), mitotic chromosomes congeal into a residual gel with apparent (phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 57 publications
(99 reference statements)
4
44
0
Order By: Relevance
“…While a majority of previously reported condensation responses occur over a timespan of minutes to hours, it is notable that our observation of HOPS, along with evidence from Cai et al, suggests that cellular response by condensation may also occur much more rapidly, at the timescale of seconds (49,91). In addition to being ubiquitous and extremely rapid, sustained HOPS influences translation of mRNA targets of microRNAs (69) and impacts cleavage and polyadenylation of nascent transcripts (49), among other gene regulatory processes (92).…”
Section: Osmotic Perturbations and The Hyperosmotic Phase Separation mentioning
confidence: 47%
“…While a majority of previously reported condensation responses occur over a timespan of minutes to hours, it is notable that our observation of HOPS, along with evidence from Cai et al, suggests that cellular response by condensation may also occur much more rapidly, at the timescale of seconds (49,91). In addition to being ubiquitous and extremely rapid, sustained HOPS influences translation of mRNA targets of microRNAs (69) and impacts cleavage and polyadenylation of nascent transcripts (49), among other gene regulatory processes (92).…”
Section: Osmotic Perturbations and The Hyperosmotic Phase Separation mentioning
confidence: 47%
“…This reveals that, while the volume is significantly altered, the relative geometric orientation of the replication-labeled chromatin remained unchanged within individual chromocenters across these three conditions ( Figure 5B). Although condensates that form by liquid-liquid phase separation usually show a sensitivity towards osmotic changes of the surrounding environment (Olins et al, 2020), the isometric contraction and expansion-behavior of the chromatin domains in this experiment resembled that of a hydrogel -not that of a liquid.…”
Section: The Effect Of Osmolarity On Intranuclear Chromatin Organizationmentioning
confidence: 55%
“…Indeed, it was recently reported that inhibition of chromatin condensation in HeLa cells on 2D substrates results in a reduction of RI and r, while inducing chromatin condensation results in the opposite effect. 28 It has been widely reported that external osmotic pressure modulates chromatin structure and aberrations [67][68][69] and more recently intracellular mass density. 15 In addition, it was shown that cancer cells under mechanical compression, actively efflux ions to decrease their intracellular tonicity in order to improve their chances of survival.…”
Section: Discussionmentioning
confidence: 99%